2017
DOI: 10.1590/es0101-73302017176604
|View full text |Cite
|
Sign up to set email alerts
|

Ensino Médio: Atalho Para O Passado

Abstract: RESUMO: Este artigo analisa a reforma do Ensino Médio proposta pela Medida Provisória nº 746/2016, na perspectiva das políticas anteriores, tais como as expressas na Lei nº 5692/1971 e no Decreto nº 2208/1997: a fusão dos ramos curriculares (pela lei) ou sua distinção (pelo decreto) tinham como função a contenção da demanda de Ensino Superior. No caso da medida provisória, essa função deriva, também, de uma particular crise das instituições privadas de Ensino Superior, que tem levado a uma inédita centralizaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 0 publications
0
7
0
17
Order By: Relevance
“…Concerning the last objective, which was to investigate the use of learning strategies in the sample, it was found that students reported making more use of metacognitive strategies, followed by the absence of dysfunctional metacognitive strategies, and cognitive strategies, respectively. This result can be considered satisfactory, since, despite the difficulties encountered in high school and now evidenced in this study (Cunha, 2017;Ramalho et al, 2018), students in this sample still seemed to be able to reflect on their learning processes and, therefore, reported making use of more complex strategies, which involves monitoring and regulating their thinking (Dembo, 1994;Weinstein et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Concerning the last objective, which was to investigate the use of learning strategies in the sample, it was found that students reported making more use of metacognitive strategies, followed by the absence of dysfunctional metacognitive strategies, and cognitive strategies, respectively. This result can be considered satisfactory, since, despite the difficulties encountered in high school and now evidenced in this study (Cunha, 2017;Ramalho et al, 2018), students in this sample still seemed to be able to reflect on their learning processes and, therefore, reported making use of more complex strategies, which involves monitoring and regulating their thinking (Dembo, 1994;Weinstein et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…The aim of this study was not to judge the proposals presented here, since the curricular organization of high school is not the focus. However, it is important to highlight that, regardless of the teaching model offered, the teacher's actions should be aligned with the expectations, motivations, and learning processes of the students themselves, which, as mentioned, affect school performance and the development of more critical, reflective, and autonomous individuals to act in society (Boruchovitch, 1999;Cunha, 2017;Ramalho et al, 2018).…”
Section: High School In Brazil: Brief Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Em um contexto nacional de aprofundamento da crise econômica no país, em que diversas medidas de cunho neoliberal vêm sendo implementadas, uma nova organização do EM é proposta, não só ignorando esses problemas reais enfrentados cotidianamente pelas escolas brasileiras, mas também, propondo uma série de mudanças no mínimo, controversas. Essas mudanças podem representar um verdadeiro "atalho para o passado" (CUNHA, 2017, p. 373), em função da retomada da sua função de contenção de acesso ao Ensino Superior, assim como em reformas anteriores (CUNHA, 2017).…”
Section: Introductionunclassified